PENINGKATAN POPULASI DAN PEMANFAATAN AYAM LOKAL BENGKULU MELALUI PENERAPAN TEKNOLOGI MIKRONUTRISI DAN PENETASAN SEDERHANA UNTUK PENINGKATAN PENDAPATAN MASYARAKAT - Nurmeiliasari .; Heri Dwi Putranto; Urip Santoso; Apri Andani (Universitas Bengkulu, 2017)
The program aims to increase the community interest to local genetic wealth of Burgochicken. The long term goal of this training is to make the village Sumber Rejo as centersof production, marketing and research activities of Burgo chicken. The method used in thisservice activity is a demonstration plot. The group is the group members who have beenprovided the knowledge and skills regarding the operation of the hatching machine. In theaspect of feed, farmers are given knowledge about the type of food, kathuk leaf supplementand ration formulation and feed mixing practices. This method is applied to support theacceleration of population growth of Burgo chicken. Extension and practice of usinghatching machine, as well as kathuk leaf extract supplementation, also introduce to targetfarmer groups as a holistic effort in increasing Burgo chicken population. Theimplementation of this activity shows some facts that (1) Burgo chicken is relatively hardto find and can be sold at high prices. (2) During the culture treatment of feed that hasbeen tested in previous studies, the production of eggs produced relatively high at anaverage of 48 eggs per head per egg-laying period, with low egg weight at an average of35 grams per egg. (3) Power of hatching eggs based on observations is still in the goodrange at 41 %. (4) The DOC mortality rate reaches 50 %. Egg production data showsgood potential. It can be seen from the total eggs produced within three months of culture(48 eggs) from five Burgo hens. High mortality and unmaximally hatchability will beincreased along with the increasing skill in the culture farming and operation of thehatching machine.Key words: Burgo Chicken, Hatching, Katuk Leaf Extract, Revenue